(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The aim of the research is to know the degree of social responsibility of employees and its impact on public relations in the Public Authority for Student Credit Fund in Damascus Governorate, and in activities and practices that embody the concept of social responsibility, and define the concept, dimensions and programs of social responsibility in the public authority. The research was based on the descriptive approach through The point of view of some managers in public relations or their representatives from among the workers. The research has appointed (54) a working manager, or whoever has deputized for them from among the workers. Main search results: 1- Clarify the concept of social responsibility and its impact on public relations in the research literature. 2- Social responsibility in public relations is based on the economic dimension, the social dimension, and the environmental dimension. 3- There are direct effects of the degree of social responsibility exemplified by the positive relationship on the material side of the public body, and indirect effects represented in a - enhancing the reputation of the public authority, b - improving the chances of obtaining capital from the competent authorities in the state, c - increasing the ability to attract workers They are highly skilled, d - improve efficiency, reduce risks and costs, and participate in training programs, e - expand market share. 4- The relationship between social responsibility and public relations emerged through three pillars: A- Media publishing, B- Sustainable community development, C- Handing out small loans to clients. 5- The most prominent activities of the Public Authority were: A- Establishing a special donation fund for people with special needs and families of martyrs, b- Small loans project for university students, C- Technology development and follow-up, and- Holding training courses based on the needs of workers in the field of the public authority. 6- One of the most important media outlets for promotion was to set up a Facebook page, flyers, and address the ministries and directorates with books explaining the work of the General Authority for the Student Credit Fund.